Optimalisasi Teknologi Informasi dan Komunikasi dalam Pendidikan Agama Islam: Peran, Dampak, dan Tantangannya - Basyari, Zen Anwar Saeful (Epistemic: Jurnal Ilmiah Pendidikan, 2022)
As society continues to evolve, the consistent growth of information and communication technology (ICT) has become imperative, particularly in the realm of education. The incorporation of ICT into educational systems is now a necessity, even within Islamic religious education, where it can significantly enhance the learning experience. This study aims to analyze the role and impact of ICT in Islamic religious education. Utilizing a qualitative approach through library research, the study explores the importance and implications of ICT in this context. Key findings reveal that while ICT facilitates learning and improves educational outcomes, it also presents certain challenges, particularly for those less adept at using technology. The study highlights the need for comprehensive training for educators and students to effectively integrate ICT into the curriculum. Furthermore, the research underscores the importance of developing tailored ICT solutions that address the unique needs of Islamic religious education. The continuous advancement of ICT necessitates its adoption in education to ensure that learning processes remain relevant and effective. This research contributes to ongoing discussions about the integration of technology in education, emphasizing its critical role in enhancing Islamic religious education while addressing potential barriers to its effective implementation.